Treatment Effect of Qingfei Paidu Decoction Combined With Conventional Treatment on COVID-19 Patients and Other Respiratory Diseases: A Multi-Center Retrospective Case Series - Zong, Xingyu; Liang, Ning; Wang, Jingya; Li, Huizhen; Wang, Dingyi; Chen, Yaxin; Zhang, Haili; Jiao, Liwen; Li, An; Wu, Guihui; Li, Jike; Wang, Mingxuan; et al. (Frontiers in Pharmacology, 2022)
Background: Qingfei Paidu decoction (QFPDD) has been widely used in treating coronavirus disease 2019 (COVID-19) in China. However, studies about the treatment effect of COVID-19 patients and other respiratory diseases have not been well demonstrated. Our study aims to determine the treatment effect of QFPDD in combination with conventional treatment on COVID-19 and other respiratory diseases. Methods: This retrospective study recruited COVID-19 patients who were treated with QFPDD for at least two courses (six days) from seven hospitals in five provinces during 21 January to 18 March 2020. Demographic, epidemiological, clinical, laboratory, laboratory, computed tomography characteristics, treatment, and outcomes data were collected and analyzed. The improvements in clinical symptoms before and after QFPDD were compared. Results: Eight COVID-19 patients were included in this study. Of them, six were males (75.0%). The median age of the patients was 66 (60-82) years. Four patients were classified as mild and moderate cases (50.0%); there were two severe cases (25.0%) and critical cases (25.0%), respectively. The most common symptom was cough (7 [87.5%]), followed by fever (6 [75.0%]), fatigue (4 [50.0%]), asthma (4 [50.0%]), and anorexia (3 [37.5%]). Abnormal findings included decreases in neutrophils (3 [37.5%]), lymphocytes (2 [25.0%]), alkaline phosphatase (3 [37.5%]), lactic dehydrogenase (4 [50.0%]), erythrocyte sedimentation rate (2 [25.0%]), and C-reactive protein (5 [83.3%]) at admission. After one course (3 days) of QFPDD, the nasal obstruction and sore throat completely disappeared, fever (5 [83.3%]), fatigue (2 [50.0%]), and cough (2 [28.6%]) were improved. After two courses (6 days), the fever disappeared completely in all patients, and the other symptoms showed a tendency to improve. 87.5% baseline symptoms in non-severe patients completely disappeared. 61.1% of the baseline symptoms of severe patients completely disappeared after patients were administered QFPDD for two courses. Of the abnormal indicators, 55.6% returned to normal levels. No serious adverse events occurred related to QFPDD during hospitalization. Conclusion: QFPDD combined with conventional treatment improved clinical symptoms in COVID-19 patients with other respiratory diseases, and no serious adverse reactions associated to QFPDD were observed. More large sample studies confirm our findings in the furfure.